A Nonuniform Sensor Distribution Strategy for Avoiding Energy Holes in Wireless Sensor Networks - Guoxi Ma; Zhengsu Tao (International Journal of Distributed Sensor Networks)
The energy hole problem exerts great impact on the energy efficiency and lifetime of wireless sensor networks (WSNs) based on many-to-one communication model. Unequal cluster emerged in recent years is a good way to alleviate the energy hole problem by dispersing cluster heads' burden. However, it fails to address this problem fundamentally due to its inherent characteristics. The single non-uniform nodes distribution strategy can alleviate the energy hole problem well by setting more nodes in networks to achieve energy balance, yet it may result in low energy efficiency and high cost of the networks. In this paper, by analyzing and minimizing intra- and inter-cluster energy consumption, we construct a suboptimal unequal cluster for WSNs. We propose a non-uniform sensor distribution strategy based on the previous unequal cluster in accordance with the energy balance principle. Simulation results show that our proposed non-uniform sensor nodes distribution strategy can not only achieve good energy efficiency as the unequal cluster method, but also ensure the network energy consumption balance and resolve the energy hole problem completely as the non-uniform sensor distribution approach. Furthermore, our algorithm needs fewer sensors to be settled than single non-uniform node distribution.